Effect of substituting concentrate with dwarf Napier grass (Pennisetum purpureum) on intake, growth and carcass composition of rabbits - Mohammad Mijanur Rahman; Mastura Nazirah Binti Mustapher; Khairiyah Binti Mat; Renny Fatmyah Utamy; Maryana Mohamad Nor (Hasanuddin Journal of Animal Science (HAJAS), 2020)
Dwarf Napier grass (Pennisetum purpureum) is considered to be more suitable as forage for ruminants due to its high yield and nutritive value, but there is limited research on rabbits. Thus, the aim of this study was to investigate the effect of replacing concentrate with dwarf Napier grass on intake, gorwth performance and carcass composition of growing rabbits. Twelve growing rabbits were randomly distributed into three dietary groups in a completely randomised design: (i) concentrate feed ad libitum as control diet (T1), (ii) half of the control diet plus dwarf Napier grass ad libitum (T2), and (iii) quarter of the control diet plus dwarf Napier grass ad libitum (T3). The results showed that diets had a significant (p<0.05) effect on intake, growth performance and some non-carcass components. Rabbits fed T3 diet showed significantly (p<0.05) lower total DM intake than those fed T1 and T2 diets. Similarly, rabbits fed T3 diet showed significantly (p<0.05) lower total weight gain and daily weight gain than those fed T1 diet, but the respective values of those fed T2 diet were non-signifiacntly different from those fed T1 and T3 diets. There was significant effect on weights of meat with bone, fat, pelt, head and kidney by the diets, whereas weights of most of the non-carcass components were similar among the groups. In conclusion, diet consisting of half of the concentrate and dwarf Napier grass ad libitum is recommended to be used as it may reduce the feed cost compared to diet consisting of the concentrate alone.